Isolating Physical Replacement of Identical IoT Devices Using Machine and Deep Learning Approaches - Mohammad, Areej Osama (2021)
A Master of Science thesis in Computer Engineering by Areej Osama Mohammad entitled, “Isolating Physical Replacement of Identical IoT Devices Using Machine and Deep Learning Approaches”, submitted in April 2021. Thesis advisor is Dr. Imran Zualkernan and thesis co-advisor is Dr. Fadi Aloul. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).